EFEKTIVITAS PEMBERIAN EKSTRAK DAUN YAKON “SMALANTHUS SONCHIFOLIUS” SEBAGAI TERAPI ANTIHIPERGLIKEMIA PADA MENCIT (MUS MUSCULUS) YANG DIINDUKSI STREPTOZOTOCIN - Triastuti, Nenny; Irawati, Detty Nur; Levani, Yelvi; Prastya, Aldo Dwi (Herb-Medicine Journal: Terbitan Berkala Ilmiah Herbal, Kedokteran dan Kesehatan, 2020)
Abstract Diabetes mellitus is an endocrine metabolite disorder characterized by hyperglycemia. This disorder is caused by demage to pancreatic beta cells or insulin resistance. According to WHO, an estimated 300 million people wordwide suffer from diabetes mellitus by 2025. The use medical drug must of course consider side effects including hypoglycemia, gastrointestinal disorders and impaired kidney function. Smalanthus sonchifolius is known to have anti-inflamatory, antioxidant and antidiabetic effects. Flavonoids as antioxidant and antidiabetic effects through several channels such as reducing apoptosis of beta pancreatic cells, promoting insulin secretion, glucose regulation on hepatocytes, reducing insulin resistance, reducing inflammation and oxidative stress on skeletal muscule cells and adipose tissue, and increasing glucose uptake in skeletal cells, This research uses a true experimental approach using the “Randomized pre and post test control group designI”. The population in this study were 28 male mice which would be divided into 4 groups, each group consisting of 7 individuals. 1 group as a control, and 3 treatment group with the administration of yakon extract each dose 200mg/KgBB, 300mg/KgBB, and 500mg/KgBB for 7 days. Of the four groups after streptozotocin induction, the highest average glucose value was 220,71mg/dl at K and the smallest value at P3 was 208,29mg/dl. While changes in the average glucose value after administration of the extract decreased, the largest value reached 50 at P3 and the smallest value at P1 which was only 36,71. Whereas in K it increased by 0,43 Key word: Diabetes Mellitus, Smalanthus sonchifolius, glucose